Diet, microbiota, and inflammatory bowel disease: lessons from Japanese foods - Kanai, Takanori (The Korean Association of Internal Medicine, 2014)
The incidence and prevalence of inflammatory bowel diseases (IBDs) including ulcerative colitis and Crohn disease are rapidly increasing in Western countries and in developed Asian countries. Although biologic agents targeting the immune system have been effective in patients with IBD, cessation of treatment leads to relapse in the majority of patients, suggesting that intrinsic immune dysregulation is an effect, not a cause, of IBD. Dramatic changes in the environment, resulting in the dysregulated composition of intestinal microbiota or dysbiosis, may be associated with the fundamental causes of IBD. Japan now has upgraded water supply and sewerage systems, as well as dietary habits and antibiotic overuse that are similar to such features found in developed Western countries. The purpose of this review article was to describe the association of diet, particularly Japanese food and microbiota, with IBD.